CHEMICAL QUALITY CHANGES AND THEIR CORRELATION TO THE SENSORY QUALITY OF SMOKED CATFISH (Hemibagrus nemurus) STORED AT ROOM AND CHILLING TEMPERATURES - Umi Habibah; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was intended to evaluate chemical quality changes of smoked catfish during storage and their correlation to sensory quality values. One hundred fish which was taken from fish culture pond in Sungai Paku were hot-smoked at 60-100oC. The smoked fish was packed in plastic bag and stored at room (28±1 oC) and chilled temperature (5±1oC) for 42 days. Changes in chemical and sensory quality were evaluated; and the values were compared. TVB, TBA, FFA and PV value of smoked fish increased during storage; and the smoked fish stored at room temperature increased faster than that stored in chilling temperature. The sensory quality value however decreased during storage. The sensory quality value of smoked fish stored at room temperature decreased faster than that stored in chilled temperature. Based on the sensory quality value, the smoked fish stored at room temperature was rejected after 14 days, and chilled temperature after 35 days. The correlation value of TVB, TBA, FFA and PV with sensory value of smoked fish stored at room temperature was 0,92; 0,97; 0,96; 0,94 respectively; and chilled temperature was 0,93; 0,87; 0,91; 0,93 respectively.Keywords: Quality, room and chilling temperatures, shelf life, smoked catfish (Hemibagrus nemurus)